MANAJEMEN PESERTA DIDIK PADA SATUAN PENDIDIKAN - Hasnadi Hasnadi (Universitas Muhammadiyah Surakarta, 2022)
Students are school inputs that affect the quality and achievement of educational goals. Differences in talents, motivations, and characteristics of students, school zoning systems, schools focus more on increasing the quantity than the quality of students, the availability of facilities and infrastructure, the number of educators and education are some of the problems related to students. These problems have an impact on the quality of graduates and the achievement of educational goals in schools. Therefore, students in educational units need to be managed properly through the concept of student management. The purpose of writing this article is to describe and analyze the management of students in the education unit. The writing of this article uses the library research method. Student management are activities carried out by schools and related to students. Activities in student management include; Planning for students (needs analysis, recruitment, selection, orientation, placement, recording and reporting of students), student development, student evaluation and student transfer. Education unit managers need to optimize the management of quality students so that students receive optimal educational services from entering school until they graduate from school.